The Mamluks, 1250-1517 - Nicolle, David 1944- (Men-at-arms series (Osprey Publishing), 1993)
Detailing their appearance and uniforms, this book describes the armies of the Mamluk Sultanate of Egypt and Syria, the power responsible for the destruction of the Crusader kingdoms